Konflik Batin Tokoh Utama pada Film "Ar Rihlah": Kajian Psikoanalisis Sastra - Rohmani, Hadad; Dayudin, Dayudin; Rohanda, Rohanda (Riwayat: Educational Journal of History and Humanities, 2025)
This research examines the inner conflict experienced by the main character, Aus, in the animated film Ar Rihlah using Sigmund Freud's psychoanalytic approach. Inner conflict is the main issue in this research because it reflects the complex psychological dynamics of the main character. This conflict is considered relevant to study because it relates to the character's moral and emotional struggles in facing the pressures of life, memories of the past, and efforts to achieve inner peace. This study focuses on the conflicts of id, ego, and super-ego, as well as the factors that trigger them and their resolution strategies. Using a qualitative descriptive method, this study analyzes narrative elements such as dialogues, monologues, and visual representations in the film. The results showed that the id conflict arose in Aus's childhood due to the pressure of living in a bandit group, while the ego and super-ego conflicts developed in adulthood due to traumatic memories of his past full of moral dilemmas. The resolution of the conflict was driven by moral support from the family and Aus's efforts to make peace with his past. This research emphasizes the importance of understanding the dynamics of human personality in a literary context, while providing insight into the emotional and moral complexities of fictional characters. By exploring these psychological layers, this research contributes to literary psychoanalysis and provides a deeper appreciation of character development in story narratives.